Treatment Evaluation of Hemodialysis Patients In General Public Hospital In Indonesia - Rohenti, Iin Ruliana (International Journal of Public Health Excellence (IJPHE), 2022)
Patients with Chronic Kidney Disease (CKD) in the final stages are indicated to obtain renal replacement therapy, namely dialysis. Dialysis is meant both peritoneal dialysis and hemodialysis. The purpose of this study is to analyze treatment in CKD patients undergoing outpatient hemodialysis at RS X. This type of research is an observational study with a cross sectional (retrospective) approach using medical record documents and patient treatment data. Analysis of the treatment uses descriptive statistic. Research data is quantitative data. The sample of the study is 74 patients. The results indicate the accuracy of the indication (100%), the accuracy of the patient (76,65%), the accuracy of the drug (79.55%), and the accuracy of the dose (96.57%).